Nurturing Entrepreneurship Ecosystem in a Developing Economy: Myths and Realities - Mubarak, Muhammad Faraz; Wan Yusoff, Wan Fauziah; Mubarik, Mobashar; Tiwari, Suman; @Ganama, Amina; A Kaya, Khalil (Journal of Technology Management and Business, 2019)
Entrepreneurship is considered as a panacea for economic infirmities. Development and prosperity can be fostered, upon the organized availability of the required resources, ambidextrously.  Entrepreneurship ecosystem is an appropriate approach where a systematic and conducive atmosphere for business activities is paved by providing support and services in the area of business policy, financing, human capital availability, infrastructure accessibility, entrepreneurial culture orientation and internationalization of indigenous products. However, despite having numerous entrepreneurship reinforce institutions, the entrepreneurship ecosystem of many developing countries is still sluggish, Pakistan is prominent among those. To improve entrepreneurship ecosystem, experts have endorsed the role of state ‘pivotal’. In this study, the entrepreneurship ecosystem of Pakistan is explored by focusing the role of government along other dimensions. For the purpose of this examination, an inductive approach was adopted in which twelve open ended interviews were conducted from policy makers, entrepreneurs, entrepreneurship professors and trade associations across the country. After thematic analysis, entrepreneurial ecosystem was found stagnant, where the role of government revealed as ambivalent, yet unfriendly and deficient. In order to develop entrepreneurship, a specific national policy for entrepreneurship should be enacted on priority and then ‘one size fit approach’ must be relinquished. Keywords: Entrepreneurship, Entrepreneurship Ecosystem, Small and Medium Enterprises, Developing Economy, SMEs